The association between self-rated eating habits and dietary behavior in two Latino neighborhoods: Findings from Proyecto MercadoFRESCO - Sharif, Mienah Z. (Prev Med Rep, 2016)
OBJECTIVE: Latinos are the largest racial and ethnic minority group in the United States and bear a disproportionate burden of obesity related chronic disease. Despite national efforts to improve dietary habits and prevent obesity among Latinos, obesity rates remain high. The objective of this study is to explore the relationship between self-rated dietary quality and dietary behavior among Latinos and how this may vary by socio-demographics to help inform future public health efforts aiming to improve eating habits and obesity rates. DESIGN: Cross-sectional study using a series of chi-square tests, the non-parametric Wilcoxon–Mann–Whitney test and logistic regression to explore self-rated eating habits. SETTING: Two urban, low-income, predominantly Latino neighborhoods in Los Angeles County. SUBJECTS: 1000 adults who self-identified as their household's primary food purchaser and preparer were interviewed from 2012 to 2013. Households were randomly selected based on their proximity to corner stores participating in a project to improve the food environment. RESULTS: Most respondents (59%) report “good” eating habits. Significant associations between “good” eating habits and overall health, fruit and vegetable consumption were observed (p < 0.001). Despite these promising findings, we also find high levels of regular soda and energy-dense food consumption. CONCLUSION: This study revealed a general understanding that healthy dietary habits are associated with fruit and vegetable consumption among Latinos in two urban neighborhoods. However, there is a need for more targeted health promotion and nutrition education efforts on the risks associated with soda and energy-dense food consumption to help improve dietary habits and obesity levels in low-income Latino communities.